PEMATAHAN DORMANSI BENIH TANJUNG (Mimusops elengi L.) SECARA FISIK DAN KIMIAWI DAN HUBUNGANNYA TERHADAP VIABILITAS DAN VIGOR - Halimursyadah Halimursyadah; Trisda Kurniawan; Nazia Ulfa (Universitas Teuku Umar, 2018)
Mimusops elengi is a medium-sized evergreen tree found in tropical forests in South Asia, Southeast Asia and Northern Australia. Its timber is valuable, the fruit is edible, and it is used in traditional medicine. As the trees give thick shade and flowers emit fragrance, it is a prized collection of gardens. The problem of this plant is its seed that has dormancy. Dormancy fulfills an important function for plants since it allows seeds to survive conditions and seasons that are unfavorable for seedling growth. This study aims to determine the interaction treatment of physical and chemical in solving dormancy on the M. elengi seed. The experiment was conducted at Laboratory of Seed Science and Technology at Juni to October 2017. There were two factors that were studied, namely the first factor of physical treatment by soaking the seeds in hot water with the level of 0, 60, 120, and 180 hours and the second factor of chemical treatment using 97% sulfuric acid with level 0, 10, 20 and 30%. The parameters measured were maximum growth potential, germination capability, vigor index, relative speed of growth, simultaneously of growth, time to reach 50% germination total and dormancy intensity. The conclusions of this study are the best soaking duration for dormancy seed breaking of M. elengi is in water at 60 °C for 180 minutes. The best concentration of sulfuric acid for breaking seed dormancy is 20%. There was a significant interaction between the duration of soaking in hot water and the concentration of sulfuric acid on all observed parameters. The best combination was found at duration of soaking of 180 minutes in hot water 60 0 C and sulfuric acid concentration 20% can accelerate germination of M. elengi seeds from 90 days (without treatment) to 24 days (after treatment). There was an increase in germination capability from 20% to 68%, maximum growth potential 73.33%, vigor index 33.33%, relative speed of growth 67.31%, simultaneously of growth 61.31%, time to reach 50% germination total 31.50 days and dormancy intensity. Keywords: Dormancy, physical and chemical, spanish cherry, viability, vigor